Evaluasi Maturitas pada Proses Incident Management dan Problem Management dalam Inflite Manager System PT. Aerofood ACS Menggunakan Framework ITIL Versi 3 Service Operation - Anvel Anvel; Yusi Tyroni Mursityo; Ismiarta Aknuranda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Recent development in business and information technology has become a waypoint for organizations to better their IT service performance. Aerofood ACS is a subsidiary of the Garuda Indonesia Group whose objective is to provide the best premium class service for food and beverage products in the in-flight catering business. Improvement of service quality has become the main goal for companies to ensure that they provide the best IT service available. Attention was brought regarding issues regarding the operational capability of previous IT services that were provided by Aerofood ACS's IT department. The previously mentioned issues often happen repeatedly because there are no right preventions or are there any controls that can be executed towards the procedures of fixing an IT service issue at Aerofood ACS. ITIL version 3 is a